Neuroprotective effect of Luteolin-7-O-Glucoside against 6-OHDA-induced damage in undifferentiated and RA-differentiated SH-SY5Y cells - Rehfeldt, Stephanie Cristine Hepp (2022)
Luteolin is one of the most common flavonoids present in edible plants and its potential benefits to the central nervous system include decrease of microglia activation, neuronal damage and high antioxidant properties. The aim of this research was to evaluate the neuroprotective, antioxidant and anti-inflammatory activities of luteolin-7-O-glucoside (Lut7). Undifferentiated and retinoic acid (RA)-differentiated SH-SY5Y cells were pretreated with Lut7 and incubated with 6-hydroxydopamine (6-OHDA). Cytotoxic and neuroprotective effects were determined by MTT assay. Antioxidant capacity was determined by DPPH, FRAP, and ORAC assays. ROS production, mitochondrial membrane potential (DYm), Caspase–3 activity, acetylcholinesterase inhibition (AChEI) and nuclear damage were also determined in SH-SY5Y cells. TNF- , IL-6 and IL-10 release were evaluated in LPS-induced RAW264.7 cells by ELISA. In undifferentiated SH-SY5Y cells, Lut7 increased cell viability after 24 h, while in RA-differentiated SH-SY5Y cells, Lut7 increased cell viability after 24 and 48 h. Lut7 showed a high antioxidant activity when compared with synthetic antioxidants. In undifferentiated cells, Lut7 prevented mitochondrial membrane depolarization induced by 6-OHDA treatment, decreased Caspase-3 and AChE activity, and inhibited nuclear condensation and fragmentation. In LPS-stimulated RAW264.7 cells, Lut7 treatment reduced TNF- levels and increased IL-10 levels after 3 and 24 h, respectively. In summary, the results suggest that Lut7 has neuroprotective effects, thus, further studies should be considered to validate its pharmacological potential in more complex models, aiming the treatment of neurodegenerative diseases.